SUFIZM IN CENTRAL ASIA: FORMATION, CHARACTERISTICS, AND ROLE IN SOCIETY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the formation of Tasawwuf and its spread in Central Asia, the prerequisites for its emergence, its significance, and stages of development. It highlights the unique features and rich history of the Sufi orders (tariqas) in the region. The development of the tariqas, the activities of the eshons, and their role in the spiritual life of the peoples of Central Asia are assessed.
Keywords: Central Asia, Islam, Tasawwuf, tariqas, asceticism, eshаn.